PENGGUNAAN METODE PEMBELAJARAN INOVATIF MELALUI STRATEGI EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN FIQH - Irfan Anshori; Heri Setiaji; Silvi Anita (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2023)
This study aims was to increase students' understanding of the practice of worship in fiqh subjects.The application of innovative learning methods through the example non example strategy is very suitable to be applied in the learning process. The example non example strategy is a learning model that uses examples. This research was conducted at MI Nambo, Pandeglang Regency. This research was conducted for 3 months, from September to November 2022. The time of this research was carried out in the odd semester of the 2022/2023 school year. This study uses experimental research methods. The type of experiment used is Quasy Experimental. The approach used in this research is a quantitative approach. In the Homogeneity Test, the results obtained were Fcount < Ftable or 1.07 < 2.215, then the data obtained was homogeneous, in the t test the results were obtained tcount=16.07 and ttable=2.044 so that the Coefficient of Determination obtained a value of 88.36, the contribution of variable X was obtained to the Y variable of 88.36% while the remainder is equal to 11.64% followed by other variables